Interplay - Adler, Ronald B (Oxford University, 2007)
Includes bibliographical references and indexes; Interpersonal process -- Culture and communication -- Communication and the self -- Perceiving others -- Language -- Nonverbal communication -- Listening: understanding and supporting others -- Emotions -- Dynamics of interpersonal relationships -- Intimacy and distance in relationships -- Communication climate -- Managing conflict